The poetics of social justice in education: an analysis of the teaching of sociology of law in the field of tension between the failure of modernity and the advance of post-modernity (Research, Society and Development, 2022)
The production and circulation of knowledge have generated various speculations in political action, in the ethical attitude and in the cultural mechanisms for the socialization of the individual as a transforming and active agent of society. Jean-François Lyotard (2015) emphasizes that the concept of postmodernity was being recycled, resignified in a rapid process of theoretical expansion, spreading beyond the academic scenario in the teaching of sociology. The general objective of this work is to recover some discussions about the great challenges in the teaching of sociology of law in contemporary society in the face of the field of tension between the epistemologies of the modern era and the issue of cultural diversity in the postmodern era. The epistemology used is inserted within the research methods of a qualitative nature, based on the literature review, focusing on the quality of sociology production until it flows into contemporary studies under the aegis of interdisciplinarity. Finally, it was concluded that the arguments made in legal science on the issue of social justice, in the current post-modern society, is a fundamental object both for the teaching of sociology of law, and for academic training focused on diversity of future professionals in legal careers.